Oceanic swarms of Antarctic krill perform satiation sinking - Tarling, Geraint A.; Thorpe, Sally E. (Proceedings of the Royal Society B: Biological Sciences, 2017)
Antarctic krill form some of the highest concentrations of animal biomass observed in the world's oceans potentially due to their prolific ability to swarm. Determining the movement of Antarctic krill within swarms is important to identify drivers of their behaviour and their biogeochemical impact on their environment. We examined vertical velocity within approximately 2000 krill swarms through the combined use of a shipborne echosounder and an acoustic Doppler current profiler. We revealed a pronounced downward anomaly in vertical velocity within swarms of −0.6 cm s −1 compared with vertical motion outside the swarm. The anomaly changed over the diel cycle, with smaller downward anomalies occurring at night. Swarms in regions of high phytoplankton concentrations (a proxy for food availability) also exhibited significantly smaller downward anomalies. We propose that the anomaly is the result of downward velocities generated by the action of krill beating their swimming appendages. During the night and in high phytoplankton availability, when krill are more likely to feed to the point of satiation, swimming activity is lowered and the anomaly is reduced. Our findings are consistent with laboratory work where krill ceased swimming and adopted a parachute posture when sated. Satiation sinking behaviour can substantially increase the efficiency of carbon transport to depth through depositing faecal pellets at the bottom of swarms, avoiding the reingestion and break-up of pellets by other swarm members.